Engineering properties and microcosmic mechanism of cement stabilized diatomite - Cui, Su Li; Tao, Zhi Peng; Zhang, Yang; Su, Hang; Jia, Yang (Frontiers in Earth Science, 2022)
In this study, the engineering properties of remolded diatomite and the effects of cement on the compression characteristic, strength properties and microstructures of cement-stabilized diatomite were investigated. Samples were prepared and stabilized with different cement content ratios, ranging from 0% to 15% by dry mass. Results show that compared with undisturbed diatomite, the compressibility of the remolded diatomite increases while the strength characteristics decrease. With the increase of cement content, the compressibility of cement-stabilized diatomite is significantly reduced and the strength characteristics are improved. Adding cement to diatomite changes the structure of pure diatomite and forms more tiny pores between cement and diatomite, while curing reduces the porosity ratio of samples and enhance the strength of cement-stabilized diatomite, especially for diatomite with higher cement content. The physical-chemical reactions including hydrolysis and hydration between cement and diatomite increase the content of sodium aluminosilicate, calcium aluminosilicate and other minerals in the soil.